An adhesion protein of Salmonella enterica serovar Typhi is required for pathogenesis and potential target for vaccine development - Ghosh, Shubhamoy (National Academy of Sciences, 2011)
More than half of all Salmonella enterica serovar Typhi genes still remain unannotated. Although pathogenesis of S. Typhi is incompletely understood, treatment of typhoid fever is complicated by the emergence of drug resistance. Effectiveness of the currently available vaccines is also limited. In search of novel virulence proteins, we have identified several putative adhesins of S. Typhi through computational approaches. Our experiment shows that a 27-kDa outer membrane protein (T2544) plays a major role in bacterial adhesion to the host through high-affinity binding to laminin. Its role in bacterial pathogenesis is underscored by reduced systemic invasion and a 10-fold higher LD(50) of the mutant bacteria in mice. T2544 is strongly immunogenic as revealed by the detection of sustained high titers of serum IgG and intestinal secretory IgA in the immunized mice. In vitro, T2544 antiserum enhanced uptake and clearance of Salmonella by macrophages and augmented complement-mediated lysis, indicating a contribution of T2544-specific antibodies to the killing process. This correlates well with the observed protection of mice immunized with recombinant T2544 or passively immunized with T2544 antiserum against subsequent bacterial challenge, suggesting that T2544-specific antibodies are involved in protection. The present study describes an adhesion protein of S. Typhi that contributes to bacterial pathogenesis. Protective antibodies in mice, rapid seroconversion of naturally infected individuals with increasing titers of anti-T2544 IgG from acute to convalescent sera suggesting antibody response in humans, and wide distribution and conservation of the cell-surface adhesin in the clinical isolates of different Salmonella serovars make T2544 a potential vaccine candidate.